Comparison of Degree of Agreement Between MRI and Histopathology in T Staging of Cervical Carcinoma - Hafiz Muhammad Huzaifah Shahid, Farah Bano, Umar Farooq (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Cervical cancer is a common disease with significant mortality and morbidity. It is due to the abnormal growth of cells that have the ability to invade or spread to other parts of the body. Objective: The main objective of the study is to compare the degree of agreement between MRI and histopathology in T staging of cervical carcinoma. Material and Methods: This cross sectional study was conducted in the department of radiology, Mayo Hospital Lahore for 12 months i.e. 12 Feb 2019 to 11 Feb 2020. MRI of the pelvis performed using a 1.5 tesla MRT 1580 scanner. All the results were interpreted by our senior radiologist and T-stage was noted according to MRI findings. All histopathological examinations performed. Both MRI and histopathology were separately place. Results: The mean age of patients was 46.45±13.38 years, 25(25%) patients were with underweight BMI and obese BMI patients were 36(36%). In our study the agreement between the MRI and histopathology was found in 77(77%) patients. Conclusion: According to our study results the MRI had good agreement with histopathology in T staging of cervical carcinoma.